Application of Fuzzy Logic to an Arduino Microcontroller-Based Egg Quality Detection Tool - M Mujiono; Nalendra, Adimas Ketut; Candrapuspa, Elok Hastari; Adimas Ketut; Elok Hastari (Generation Journal, 2023)
The process of selecting good eggs that are suitable for consumption is usually carried out using the candling method manually or by observing using a light or flashlight, then observing with the eyes. This method has weaknesses, because manual observations take a long time and the possibility of errors. it is necessary to make a tool that can efficiently detect eggs, using a Light Dependent Resistor (LDR) sensor and an Arduino. LDR Sensor is used to capture the intensity of light, which is emitted into the egg, then processed using Arduino basic for decision maker with fuzzy logic. This tool works with the results of the LDR sensor and displayed on the LCD and color LEDs. Based on the experimental results obtained that the accuracy of the tool is 95%